Using mechanical modelling and experimentation for the conservation of musical instruments - Le Conte, Sandie; Le Moyne, Sylvie; Ollivier, François; Vaiedelich, Stéphane (Journal of cultural heritage, 2012)
The Musée de la musique in Paris keeps a collection of more than 4500 musical instruments. Many of them are subject to investigations aiming at improving their conservation conditions. The approach to study these cultural heritage objects is pluridisciplinary, combining material analysis, research of historical context, and mechanical aspects. This paper focuses on the application of dynamical mechanics to a case study, the restoration to playable state of a historical harpsichord. The mechanical model supported the decision for the “best” restoration and conservation conditions.